The external dimension of EU private international law after opinion 1/13 / edited by Pietro Franzina. - Franzina, Pietro (Intersentia, 2017)
The interest of the EU in international efforts towards the harmonisation of private international law has steadily increased over the years. The EU is already a party to several conventions that lay down uniform rules on jurisdiction, conflicts of laws and the recognition and enforcement of judgments. Additionally, various international instruments dealing with judicial cooperation in civil matters have been ratified by the Member States 'in the interest of the Union', or are now administered by the EU. On different occasions the Court of Justice has expressed its views regarding the scope of the external competence of the Union in the field of private international law, the conditions upon which this competence should be regarded as exclusive and the principles according to which the competence itself should be exercised. In spite of this, the development of the external dimension of EU private international law remains a controversial topic, and different questions still await answers. The essays collected in this volume critically address some of the main issues concerning the relations of the EU with non-EU countries and international organisations in the area of private international law, as well as the impact of these relations on EU legislation dealing with matters featuring cross-border implications. Written by leading legal scholars for academics and practitioners, the book discusses, in particular, the principles stated in the latest intervention of the Court of Justice on this topic, Opinion 1/13, regarding the Union's competence as to the acceptance of the accession of third States to the Hague Convention of 1980 on international child abduction, as well as the implications of the Opinion for the development of the EU's external action and legislation in this area.With contributions by Paul Beaumont, Marise Cremona, Serena Forlati, Pietro Franzina, Giorgio Gaja, Jan-Jaap Kuipers, Fabrizio Marongiu Buonaiuti, Alex Mills, Chris Thomale, Chiara E. Tuo, Karen Vandekerckhove and Alessandra Zanobetti.About the editorPietro Franzina is Associate Professor of International Law at the Department of Law of the University of Ferrara.